Magnetic resonance imaging findings of high-grade ductal carcinoma in situ of the male breast: A case report - Florian Reinhardt; Britta Mathys; Petra Reinecke; Hans Neubauer; Tanja Fehm; Svjetlana Mohrmann (SAGE Open Medical Case Reports, 2018)
Ductal carcinoma in situ in men is incredibly rare and detection by conventional mammography and ultrasound is often challenging. We report an unusual case of a 50-year-old male, with no family history of breast cancer, who presented with an 8-year history of left-sided breast pain and recurrent bloody nipple discharge without any significant suspicious imaging features in mammography and targeted high-resolution ultrasound. Breast magnetic resonance imaging was performed as an adjunct modality. Magnetic resonance imaging findings revealed a suspicious retroareolar non-mass abnormality of segmental, linear and dendritic pattern, which was highly suspicious for a ductal carcinoma in situ. Stereotactic guided biopsy and subsequent mastectomy were consistent with pure high-grade ductal carcinoma in situ of the left breast. Overall, this case highlights the challenges in diagnosing ductal carcinoma in situ in men and demonstrates the importance for further investigating clinical suspicions of the male breast.